Tax Administration and Entrepreneurial Performance: A Study of SMEs in Uganda - Kintu, Ismail; Buyinza, Faisal; Kiwala, Yusuf (International Business Research, 2019)
Using the 2013 World Bank Enterprise Survey Data for Uganda, this paper employs the logit and quintile estimation technique to explain the relationship between tax administration and entrepreneurial performance among SMEs in Uganda. The study also employed interviews to obtain expert opinion about tax administration and also explain the results of logit models. Our results indicate that tax rate positively and significantly affect entrepreneurial performance, while tax administration has no effect on entrepreneurial performance. Other key factors that promote entrepreneurial performance include access to credit, firm age, male ownership, training and participation in exporting. Our results suggest that efforts to incentivize and set a conducive tax rate, ease of access to financing and training need to be strengthened for higher entrepreneurial performance among SMEs in Uganda.
Keywords: tax administration, SME performance, Uganda